Community-wide versus school-based targeted deworming for soil-transmitted helminth control in school-aged children in Vietnam: the CoDe-STH cluster-randomised controlled trialResearch in context - Clare E.F. Dyer; Dinh Ng-Nguyen; Naomi E. Clarke; Sze Fui Hii; Hieu Quoc Nguyen; Van-Anh Thi Nguyen; Thai Van Nguyen; Trong Van Nguyen; Tam Thi Ngo; H.M.P. Dilrukshi Herath; Handan Wand; Luc E. Coffeng; et al. (Elsevier, 2023)
Summary: Background: Soil-transmitted helminth (STH) infection control programs typically consist of school-based preventive chemotherapy (PC) targeted to school-aged children. STH reservoirs in untreated community members contribute to ongoing transmission in children. The CoDe-STH (Community Deworming against STH) trial, conducted in Dak Lak province, Vietnam, between October 2019 and November 2020, aimed to determine whether community-wide mass drug administration (MDA) is more effective than school-based targeted PC in reducing STH prevalence and intensity in children. Methods: In this two-arm cluster randomised controlled trial, 64 primary schools were randomly assigned 1:1 to receive either school-based targeted PC ("school arm") or community-wide MDA ("community arm"). A single dose of albendazole 400 mg was used for deworming. The primary outcome was hookworm prevalence in schoolchildren, measured using quantitative real-time PCR. We also measured infection intensity for Necator americanus only, using qPCR cycle threshold (Ct) values converted into eggs per gram of faeces (EPG). Analysis was by intention to treat. The trial was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12619000309189). Findings: The analysis included 4955 children in the school arm and 5093 children in the community arm. N. americanus was the dominant STH species. The relative reduction in hookworm prevalence was not significantly different between the school arm (30.1%, 95% confidence interval [CI] 20.5-36.9) and the community arm (34.6%, 95% CI 19.9-49.4). Due to lower baseline prevalence than expected, the study was underpowered to detect a difference in prevalence reduction between the study arms. The community arm showed significantly greater relative reduction in N. americanus infection intensity (56.0%, 95% CI 39.9-72.1) compared to the school arm (3.4%, 95% CI −24.7 to 31.4). The community arm also showed greater relative reduction in prevalence of moderate-to-heavy intensity (≥2000 EPG) N. americanus infections (81.1%; 95% CI 69.7-92.6) compared to the school arm (39.0%, 95% CI 13.7-64.2). Interpretation: Although no impact was seen on overall prevalence, community-wide MDA was more effective in lowering N. americanus infection intensity in schoolchildren compared to school-based targeted PC, measured 12 months after one round of albendazole deworming with high coverage. Funding: National Health and Medical Research Council, Australia (APP1139561).